Tutorials as aflexible alternative to GUIs: An example for advanced model calibration using Pilot Points - Moeck, Christian; Hunkeler, Daniel; Brunner, Philip (My University, 2015)
Environmental modelling software with graphical user interfaces (GUIs) are user friendly and help tofocus on the aspects of modelling rather than on the technicality of the underlying code. This is afundamental advantage compared to codes without a GUI, as the absence of a GUI can prohibit thewidespread application of a software tool. However, there is a downside to GUIs, too. They commonly lagbehind the newest software development. We argue that tutorials are aflexible but undervaluedalternative to GUIs, and are convinced that tutorials can help to make complex software accessible to anincreased number of users. As an example to demonstrate our point, we have written a tutorial thatillustrates the use of Pilot-Point based calibration made available through PEST in the HydroGeoSpheremodelling environment. We hope that this example will encourage the modelling community to developtutorials and make them available to the wider public.
Keywords: GUI; Tutorial; Model calibration; Pilot Points; HydroGeoSphere